Rancang Bangun Alat Deteksi Hipotermia berdasarkan Detak Jantung dan Suhu Tubuh dengan Metode Fuzzy Tsukamoto - Henry Trenggana; Edita Rosana Widasari; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Hypothermia is a condition where the body temperature is below average and the body does not have the ability to produce heat properly due to a weakened heart rate and common in climbers who climb mountain. Hypothermia can be dangerous if not treated immediately because people with hypothermia usually don't know that they have hypothermia. In this study, a tool was designed to detect hypothermia with classfication method using the Fuzzy Logic Tsukamoto Method. Fuzzy input come from the MAX30102 sensor to calculate the number of heartbeats, and the DS18B20 sensor to calculate body temperature. Because the tool will be used in climbing areas that have limited power sources, the tool requires a mechanism to save its power. In this study, the low power mode mechanism is used which is applied to the ATmega328P. When the tool is not in use, the system goes into sleep mode and will return to wake mode if the trigger made of a push button is pressed. This system has 2 components that function as output, the 128x32 OLED used to display sensor readings and classification results and a buzzer that will emit a sound if the user is detected to have hypothermia. This study obtained an accuracy of 96.45% on the MAX30102 sensor in the heart rate reading test. In testing the temperature readings, this study obtained an accuracy of 99.41%. In testing the accuracy of the Fuzzy Tsukamoto Method, a value of 100% was obtained with an average computation time of 395.6 Âµs. As well as the low power mode mechanism which has managed to reduce the average current usage by up to 72.2%.